2019
DOI: 10.1111/cdoe.12463
|View full text |Cite
|
Sign up to set email alerts
|

A life course approach to total tooth loss: Testing the sensitive period, accumulation, and social mobility models in the Health and Retirement Study

Abstract: Objectives: Childhood socio-economic status (SES) has long been associated with later-life oral health, suggesting that childhood is a sensitive period for oral health.Far less attention has been given to the long-term impact of childhood trauma, abuse, and smoking on later-life oral health. This study fills the gap in the literature by examining how adverse childhood experiences-social, psychological, and behavioralshape total tooth loss over the life course, with an assessment of the sensitive period, accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…They suggest that any form of social mobility (either upward or downward) might positively impact adult perceptions of oral health, probably because mobile individuals seek to maximise their status [9,38]. The positive effect of downward social mobility found in this study contrasts with previous dental studies that reported a negative association between downward mobility and good oral health [11][12][13][14][15][16][17][18][19][20][21]. The fact that downward mobility was inversely associated with poor oral health implies that there will be more people with good oral health in the lower social class.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…They suggest that any form of social mobility (either upward or downward) might positively impact adult perceptions of oral health, probably because mobile individuals seek to maximise their status [9,38]. The positive effect of downward social mobility found in this study contrasts with previous dental studies that reported a negative association between downward mobility and good oral health [11][12][13][14][15][16][17][18][19][20][21]. The fact that downward mobility was inversely associated with poor oral health implies that there will be more people with good oral health in the lower social class.…”
Section: Discussionmentioning
confidence: 73%
“…The effect of social mobility on adult oral health has been investigated in several longitudinal studies, although most have focused on intergenerational mobility [11][12][13][14][15][16][17][18][19][20]. Only two previous studies have looked at intragenerational mobility in relation to oral health [12,21].…”
Section: Introductionmentioning
confidence: 99%
“…1). Of the 21 articles, 18 provided sufficient data for meta-analysis after the authors were contacted for further information (Osler et al 2009; Pearce et al 2009; Bernabé et al 2011; Tsakos et al 2011; Yiengprugsawan et al 2011; Thomson 2012; Celeste et al 2013; Åström et al 2015; Peres et al 2016; Han and Khang 2017; Celeste and Fritzell 2018; Fantin et al 2018; Goettems et al 2018; Listl et al 2018; Ramsay et al 2018; Vendrame et al 2018; Lee 2019; Nascimento et al 2020), and 3 were included in the qualitative analysis (Brennan and Spencer 2015; de Andrade et al 2018; Zhang and Chen 2019). To increase homogeneity within studies, larger data sets were split by country (Listl et al 2018), age group (Yiengprugsawan et al 2011; Peres et al 2016; Celeste and Fritzell 2018), or specific group (e.g., twins; Osler et al 2009); therefore, the statistical analysis was performed with 40 analytic data sets.…”
Section: Resultsmentioning
confidence: 99%
“…All models included demographic covariates including age in years, gender (1 = female), and race/ethnicity in four categories, non-Hispanic white (reference), non-Hispanic Black, Hispanic, and other. Following the previous work (Lee, 2019; Luo & Waite, 2005; Zhang et al, 2016), we also controlled for childhood health, as it is closely related to later cognition, using the question: “from age 6 to 16 years, would you say that your health during that time was excellent, very good, good, fair, or poor?” Respondents who reported that they had “fair” or “poor” health were compared to those whose health was “excellent,” “very good,” or “good.”…”
Section: Methodsmentioning
confidence: 99%